PENGARUH PROFITABILITAS, KECUKUPAN MODAL, DANA CADANGAN DAN TINGKAT SUKU BUNGA TERHADAP KREDIT BERMASALAH PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Utami, Dean Aghitna (Jurnal Akuntansi AKUNESA, 2020)
This study aims to examine the effect of profitability, capital adequacy, loan losses reserve, and interest rate on non performing loan. The samples that used in this research are commercial banks listed on the Indonesian Stock Exchange during the period 2014-2017. The samples are chosen by the using purposive sampling technique. Data were analyzed using multiple linear regression. The results showed that profitability, capital adequacy, loan losses reserve, and interest rate has affected on non performing loan.